2016
DOI: 10.1002/jcc.24375
|View full text |Cite
|
Sign up to set email alerts
|

Converging ligand‐binding free energies obtained with free‐energy perturbations at the quantum mechanical level

Abstract: In this article, the convergence of quantum mechanical (QM) free‐energy simulations based on molecular dynamics simulations at the molecular mechanics (MM) level has been investigated. We have estimated relative free energies for the binding of nine cyclic carboxylate ligands to the octa‐acid deep‐cavity host, including the host, the ligand, and all water molecules within 4.5 Å of the ligand in the QM calculations (158–224 atoms). We use single‐step exponential averaging (ssEA) and the non‐Boltzmann Bennett ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(107 citation statements)
references
References 81 publications
(234 reference statements)
0
106
1
Order By: Relevance
“…1), without changing the relative binding free energies of the ligands by more than 2 kJ/mol [72]. In fact, as shown in Table S1 in the Supplementary material, the 2 kJ/mol difference comes mainly from the propionate ligand.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1), without changing the relative binding free energies of the ligands by more than 2 kJ/mol [72]. In fact, as shown in Table S1 in the Supplementary material, the 2 kJ/mol difference comes mainly from the propionate ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Test calculations on the SAMPL4 ligands with FES methods showed that these charged groups had only minimal effects (<2 kJ/mol) on the relative binding free energies [72]. Unfortunately, the structures of the neutralised host were more distorted than those of the charged host, probably owing to the repulsion of the charged groups in the vacuum optimisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The applicability of this approach is limited by the overlap between QM and MM potential energy surfaces, and the size of the system of interest, because of this, alternative free energy schemes may be preferable. Dybeck et al [2016]; Jia et al [2016]; Ryde and Söderhjelm [2016]; König and Brooks [2015]; Cave-Ayland et al [2014]; Sampson et al [2015]; Rodinger and Pomès [2005]; Heimdal and Ryde [2012]; Mikulskis et al [2014]; Genheden et al [2015]; Olsson et al [2016]; Hudson et al [2015a,b]; Beierlein et al [2011]; Fox et al [2013]…”
Section: Methodsmentioning
confidence: 99%